ANALYSIS OF FACTORS INFLUENCED IN THE DEVELOPMENT OF THE POULTRY INDUSTRY - Hayitnazarova , Holida (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
This thesis examines the theoretical and methodological foundations of strategic development of the poultry industry. The development strategy of the poultry sector is interpreted as a process of rational resource allocation, implementation of a set of measures, and ensuring sustainable development of poultry farms in the long term. The social, economic, organizational, and technical characteristics of the poultry industry and its role within the agro-industrial complex are analyzed. Particular attention is paid to the high productivity of poultry farming, feed conversion efficiency, and the importance of egg and meat production in ensuring food security. The current state and structural composition of the poultry industry in Uzbekistan are reviewed based on statistical data. The research findings provide a methodological basis for developing effective strategies for the sustainable development of the poultry sector.